Effectiveness of warm-up and dynamic balance training in preventing anterior cruciate ligament injuries in college gymnasts: a 3-year prospective study for one team - Muramoto, Y.; Iwamoto, W.; Iida, S.; Sasagawa, K.; Kobayashi, H.; Ishibuchi, S.; Murakami, J.; Maehara, Y.; Tanaka, N.; Wagatsuma, K.; Kuruma, H. (The Journal of Sports Medicine and Physical Fitness, 2024)
BACKGROUND: The effect of trunk stability and dynamic balance warm-up exercises on physical functional improvement remains unelucidated. This study examined whether exercises could prevent anterior cruciate ligament (ACL) injury and improve trunk muscle activation and dynamic balance in gymnasts. METHODS: This comparison study, involving gymnastics practice sessions, included 31 university gymnasts and was conducted in two periods: 1 year of observation followed by 2 years of intervention. Participants performed a trunk and dynamic balance warm-up exercise program during the intervention. The effect of exercise on the incidence of ACL injury was evaluated. In addition, the paired t-test was used to compare the Y-balance distance and the changes in muscle thickness associated with trunk muscle activation at rest and during plank. RESULTS: ACL injury risk during the intervention was significantly lower, with a relative risk of 0.23 (P=0.02, 95% CI: 0.06-0.88). Changes in muscle thickness with activation of the transversus abdominis (P<0.01, mean difference 4.1, 95% CI: 9.97-28.07, Cohen`s d=0.52), internal oblique (P<0.01, mean difference 5.2, 95% CI: 9.72-21.55, Cohen`s d=0.65), and external oblique (P<0.01, mean difference 5.5, 95% CI: 20.44-39.09, Cohen`s d=0.71) muscles were significantly higher during the intervention. The Y-balance distance was also significantly greater in the posterior medial reach (P<0.01, mean difference 3.3, 95% CI: 1.56-6.26, Cohen`s d=0.46) during the intervention. CONCLUSIONS: Exercise-based warm-up programs may decrease ACL injuries. It can improve physical functions, such as the rate of change in trunk muscle thickness and the posterior medial distance during Y balance.